The Education Resilience of Out-of-school Children in Bhutan : A Methodology and Pilot Study - World Bank (Washington, DC, 2015)
Accessibility and quality of education is a much-debated issue today. In Bhutan this is especially a concern for the population scattered across the extreme mountainous terrain of the country. Difficult access and spatial isolation leads to an unequal distribution of the quality services in Bhutan. It is also an issue for children in urban communities despite the easy access to schools. Poverty and disability hold children back from enrolling in and completing school. Hence, the education resilience in these vulnerable communities can differ accordingly even despite the fact that the government provides free basic education in Bhutan. We define resilience as the ability of students, education institutions, and communities to achieve positive education outcomes in spite of adversities, such as the marginalization, isolation and poverty that exist in pockets in Bhutan. This report presents the results of our pilot study. We consulted with education policy makers and implementers at the national level, and communities, parents and children themselves at the local level, to conduct an in-depth analysis of the risks and the assets (strengths, opportunities and resources), that exist in schools, homes and in communities. Accordingly, recommendations are also made in this report with a view towards filling the gaps and enhancing the relevance of education policies and programs based on the evidence collected from the field during the study.